Word 2010 all-in-one for dummies - Lowe, Doug, 1959- (--For dummies., 2010)
Reviews fundamentals of Word 2010 while demonstrating the word processing program's updated features and explaining how to integrate documents with other Microsoft Office applications, customize the program, post documents to the Web, add graphics, program with VBA, and edit and format text.